The competitiveneá of African pigeonpea exports in International markets - Lo Monaco, G. (Bulawayo (Zimbabwe), 2003)
Sumario (En)
Ilus.; 27 ref.
Keywords: MERCADOS MUNDIALES; DATOS GLOBALES; CONSUMO; COMERCIO; EXPORTACIONES; PRECIOS; CALIDAD; AFRICA